2005
DOI: 10.1136/emj.2003.013979
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of victims of violence admitted to an emergency department

Abstract: Objective: To collect data on the consultation frequency and demographic profile of victims of violence attending an emergency department (ED) in Switzerland. Methods: We undertook screening of all admitted adult patients (.16 years) in the ED of the CHUV, Lausanne, Switzerland, over a 1 month period, using a modified version of the Partner Violence Screen questionnaire. Exclusionary criteria were: life threatening injury (National Advisory Committee on Aeronautics score >4), or inability to understand or spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
(7 reference statements)
2
19
0
5
Order By: Relevance
“…2 Of all women treated in emergency departments (EDs), it is estimated that 2.2% to 12% present with injuries related to acute IPV. [3][4][5][6][7] IPV is associated with increased risk of a number of physical and mental illnesses, so emergency physicians (EPs) and staff are likely to see victims of IPV in their daily practice. 1,8 Femicide (murder of females) is the most severe outcome of IPV.…”
mentioning
confidence: 99%
“…2 Of all women treated in emergency departments (EDs), it is estimated that 2.2% to 12% present with injuries related to acute IPV. [3][4][5][6][7] IPV is associated with increased risk of a number of physical and mental illnesses, so emergency physicians (EPs) and staff are likely to see victims of IPV in their daily practice. 1,8 Femicide (murder of females) is the most severe outcome of IPV.…”
mentioning
confidence: 99%
“…Auch Untersuchungen außerhalb Deutschlands zum Thema körperliche und sexuelle Gewalt zeigten, dass lediglich 1-13% der betroffenen Patientinnen jemals auf dieses Thema von ihrem Hausarzt angesprochen werden [13,14]. Gründe, welche die Erstversorgenden trotz einer geschätzten Prävalenz von 30% von einem routinemäßigen 7 Screenen auf häusliche Gewalt [15] abhalten, liegen nach Meinung von Waalen et al [16] zum einen im Mangel an Zeit, zweitens im Mangel an Beweisen, dass Interventionen von Erfolg gekrönt sind, und drittens im Mangel an Aufklärung über die Prävalenz und die Bedeutung häuslicher Gewalt.…”
Section: Gesprächsführung Bei Verdacht Auf Gewalterfahrungunclassified
“…It is estimated that in the USA 28% of women who suffer injuries as a consequence of IPV will receive medical care and in more than 50% of the cases this care will be given at the emergency unit of a hospital (National Center for Injury Prevention andControl 2003, Lipsky &Caetano 2007). A Canadian study (MacMillan et al 2006) reported 11.3% to 17.7% twelve-month prevalence rates among patients screened for IPV in two emergency units, while a similar study in Switzerland (Hofner et al 2005) reported a 11.4% prevalence rate.…”
Section: Introductionmentioning
confidence: 99%